Incidence and Predictors of Pre-Eclampsia Among Pregnant Women Attending Antenatal Care at Debre Markos Referral Hospital, North West Ethiopia: Prospective Cohort Study - Birhanu MY; Temesgen H; Demeke G; Assemie MA; Alamneh AA; Desta M; Toru M; Ketema DB; Leshargie CT (Dove Medical Press, 2020)
Molla Yigzaw Birhanu,1 Habtamu Temesgen,2 Gebreselassie Demeke,3 Moges Agazhe Assemie,4 Alehegn Aderaw Alamneh,2 Melaku Desta,5 Milkiyas Toru,3 Daniel Bekele Ketema,4 Cheru Tesema Leshargie1 1Department of Public Health, College of Health Sciences, Debre Markos University, Debre Markos, Ethiopia; 2Department of Human Nutrition and Food Sciences, College of Health Sciences, Debre Markos University, Debre Markos, Ethiopia; 3Department of Medical Laboratory Sciences, College of Health Sciences, Debre Markos University, Debre Markos, Ethiopia; 4Department of Public Health, College of Health Sciences, Debre Markos University, Debre Markos, Ethiopia; 5Department of Midwifery, College of Health Sciences, Debre Markos University, Debre Markos, EthiopiaCorrespondence: Molla Yigzaw BirhanuCollege of Health Sciences, Debre Markos University, P.O. Box 269, Debre Markos, EthiopiaEmail mollayigzaw33@gmail.comBackground: Pre-eclampsia is a pregnancy-induced hypertension that occurs after 20 weeks of gestation. It is the leading cause of maternal and perinatal morbidity and mortality globally, but it is higher in developing countries. In Ethiopia, conducting research on the incidence and predictors of pre-eclampsia is crucial due to the paucity of information.Methods: A prospective cohort study was undertaken using 242 pregnant women between November 1, 2018 and March 30, 2019 at Debre Markos Referral Hospital. All eligible women who fulfilled the inclusion criteria were included in this study. Data were entered into the epic-data Version 4.2 and analyzed using the STATA Version 14.0 software. The Cox-proportional hazard regression model was fitted and Cox-Snell residual test was used to assess the goodness of fit. Pre-eclampsia free survival time was estimated using the Kaplan–Meier survival curve. Both bivariable and multivariable Cox-proportional hazard regression models were fitted to identify predictors of pre-eclampsia.Results: The overall incidence rate of pre-eclampsia was 3.35 per 100 person-years. Having a pre-existing history of diabetes mellitus [AHR=2.7 (95% CI=1.43– 8.81)], having a history of multiple pregnancy [AHR=3.4 (95% CI=2.8– 6.9)] and being ≥ 35 years old age [AHR=2.5 (95% CI=1.42– 3.54)] were the significant predictors of pre-eclampsia.Conclusion: The incidence of pre-eclampsia was high in this study. Having (pre-existing diabetes and multiple pregnancy) and being ≥ 35 years old age were the significant predictors of pre-eclampsia. Inspiring pregnant women’s health-seeking behavior should provide a chance to diagnose pre-eclampsia early to prevent the medical complication of pre-eclampsia.Keywords: pre-eclampsia, incidence, predictors, pregnant women, Debre Markos, Ethiopia